2017
DOI: 10.3126/jcmsn.v13i2.17711
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of palatal rugae as an indicator of identification in young adults of Nepal

Abstract: Background & Objectives:The cur r ent study was conducted to identify and determine the association between gender and characteristics of palatal rugae in Nepalese population. Materials & Methods: Characteristics of palatal rugae including number, length, shape, direction and unification were analyzed in 100 maxillary dental plaster casts. Association between palatal rugae and gender were tested using chi square analysis and statistical descriptors were identified using SPSS 10.0 keeping the level of statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…On comparing the angulation of palatal rugae between the males and females on the right side of palate, we found that while comparing among those with zero angulation (perpendicular rugae), the mean of female participants was found to be higher than males ( P = 0.015). Similar findings were obtained by Shrestha et al in 2017[ 11 ] and Pramanik et al in 2019. [ 13 ]…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…On comparing the angulation of palatal rugae between the males and females on the right side of palate, we found that while comparing among those with zero angulation (perpendicular rugae), the mean of female participants was found to be higher than males ( P = 0.015). Similar findings were obtained by Shrestha et al in 2017[ 11 ] and Pramanik et al in 2019. [ 13 ]…”
Section: Discussionsupporting
confidence: 90%
“…This may be attributed to the fact that the length of palatal rugae undergoes a change, when changes occur in palatal bone with the increasing age of individual. [ 11 ] Reason behind more primary rugae length in males than females was higher arch length in male subjects as compared to the females. [ 11 12 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation